Caudal cervical vertebral morphological variation is not associated with clinical signs in Warmblood horses. (16th July 2019) - Veraa, S.; de Graaf, K.; Wijnberg, I. D.; Back, W.; Vernooij, H.; Nielen, M.; Belt, A.J. M.
Summary: Background: Variation in equine caudal cervical spine morphology at C6 and C7 has high prevalence in Warmblood horses and is suspected to be associated with pain in a large mixed‐breed group of horses. At present no data exist on the relationship between radiographic phenotype and clinical presentation in Warmblood horses in a case‐control study. Objectives: To establish the frequency of radiographically visible morphologic variation in a large group of Warmblood horses with clinical signs and compare this with a group without clinical signs. We hypothesised that occurrence of morphologic variation in the case group would not differ from the control group, indicating there is no association between clinical signs and morphologic variation. Study design: Retrospective case‐control. Methods: Radiographic presence or absence of morphologic variation of cervical vertebrae C6 and C7 was recorded in case (n = 245) and control horses (n = 132). Case and control groups were compared by univariable Pearson's Chi‐square and multivariable logistic regression for measurement variables age, sex, breed, degenerative joint disease and morphologic variation at C6 and C7. Odds ratio and confidence intervals were obtained. A P≤0.05 was considered statistically significant. Results: Morphologic variation at C6 and C7 (n = 108/377 = 28.6%; Cases 58/245 = 23.7%; Control 50/132 = 38%) was less frequent in horses with clinical signs in univariable testing (OR 0.48, 95% CI 0.3–0.8, P = 0.001). Age, sex, breed and degenerative joint disease were not retained in the final multivariable logistic regression step whereas morphologic variation remained significantly less present in horses with clinical signs. Main limitations: Possible demographic differences between equine clinics. Conclusions: Morphologic variation in the caudal cervical spine was detected more frequently in horses without clinical signs. Therefore, radiographic presence of such variation does not necessarily implicate the presence of clinical signs.